Academician Evgeny Pavlovich Velikhov and computer optics. Issue 1 (February 2021) - Kazanskiy, N L
Abstract: The article describes the role played by Academician Evgeny P. Velikhov in the development of the scientific direction "computer optics". It talks about the creation of the journal "Computer Optics", the establishment of the Research & Education Center "Spectrum", the support of the Image Processing Systems Institute of the RAS.